(untitled) (European Journal of Pure and Applied Mathematics, 2017)
For square contingency tables with ordered categories, we decompose the symmetry model into three models for cumulative probabilities.Three models are the cumulative two ratios-parameter symmetry, the global symmetry, and the marginal means equality models.An example is given.